Chitosan-sodium alginate double-layer membrane with pH value indication function and preparation method thereof

By using a double-layer film structure of sodium alginate loaded with anthocyanins in food packaging, combined with the ultraviolet blocking function in the chitosan layer, the problem of poor anthocyanin structural stability is solved and the stability of the pH indicating film is achieved. And the use time is improved to effectively monitor the freshness of meat products.

CN115743924BActive Publication Date: 2025-01-17TAIYUAN UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202211560505.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-07
Publication Date
2025-01-17
Estimated Expiration
2042-12-07

AI Technical Summary

Technical Problem

In the prior art, anthocyanins as pH indicators have poor structural stability in food packaging, resulting in low stability of pH indicators, making it difficult to effectively monitor the freshness of meat foods.

Method used

Sodium alginate is used as the matrix to load anthocyanins in a double-layer membrane structure. The molecular chain structure of sodium alginate has a responsive effect on the pH value. It fixes anthocyanins in an acidic environment and releases anthocyanins when the pH value changes. Functional components that block or absorb ultraviolet rays are added to the chitosan layer to improve the stability of anthocyanins.

Benefits of technology

It achieves stable loading and effective release of anthocyanins, extends the use time of the pH indicating film, and improves the ability to monitor food freshness in real time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115743924B_ABST
    Figure CN115743924B_ABST
Patent Text Reader

Abstract

The invention discloses a chitosan-sodium alginate double-layer membrane with a pH value indicating function and a preparation method thereof. In the double-layer membrane, anthocyanin is loaded on a sodium alginate matrix as an inner layer of an indicating membrane, and a functional component having the function of preventing or absorbing ultraviolet rays is added to chitosan as an outer layer of an indicating membrane; the functional component is one or more of titanium dioxide, silicon dioxide or zinc oxide. The preparation method of the double-layer membrane is to prepare sodium alginate and anthocyanin film-forming liquid, chitosan and functional component film-forming liquid respectively, and then obtain the chitosan-sodium alginate double-layer membrane by a layer-by-layer casting film-forming method, an extrusion method or a layered film-forming method. The sodium alginate layer in the double-layer membrane of the present invention utilizes sodium alginate and anthocyanin to realize the pH value indicating function, and the functional component of the chitosan layer can reduce the influence of ultraviolet light on the action of anthocyanin, enhance the stability of anthocyanin, increase the utilization rate of anthocyanin, and make the chitosan-sodium alginate double-layer membrane have a long-term and stable pH value indicating effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a chitosan-sodium alginate double-layer film with a pH value indicating function and a preparation method thereof, belonging to the technical field of intelligent food packaging materials and preparation thereof. Background Art

[0002] Meat and seafood are rich in trace elements and high protein required by the human body, but they are easy to spoil. Foodborne pathogens caused by food spoilage can endanger human health. The pre-determined shelf life based on experience cannot provide real-time freshness of food, which will lead to the accidental ingestion of spoiled food or waste of food. During the spoilage process of meat food, a large amount of ammonia and amine volatile alkaline substances are produced due to the decomposition of protein, resulting in an alkaline atmosphere in the packaging headspace. These alkaline atmospheres can change the pH value of the food microenvironment. Therefore, food packaging films with pH indication can display the freshness of such foods in real time.

[0003] Anthocyanins are a class of water-soluble natural pigments widely found in plants. They are positively charged under acidic conditions, and their molecular structure changes with pH, ​​causing them to show different colors at different pH values. Compared with natural pigments such as curcumin, betaine and shikonin, anthocyanins show richer colors at different pH values, so anthocyanins are an ideal pH indicator. However, anthocyanins are easily degraded by ultraviolet rays, temperature and oxygen, among which ultraviolet rays have the most significant effect on the stability of anthocyanins.

[0004] Chinese patent CN114409975A discloses a chitosan-blueberry anthocyanin edible film with chitosan as the base material and blueberry anthocyanin added; Chinese patent CN113045802A uses blueberry anthocyanin and starch as the main film-forming materials, and uses a binder and a plasticizer as auxiliary materials to prepare a solution, and then casts the film to obtain a blueberry anthocyanin edible composite film. However, the anthocyanin structure stability in these films is poor, which reduces the stability of the pH value indication function of the film. Summary of the invention

[0005] The present invention aims to provide a chitosan-sodium alginate double-layer membrane with pH value indicating function and a preparation method thereof. The chitosan-sodium alginate double-layer membrane with pH value indicating function comprises a sodium alginate matrix loaded with anthocyanin as an inner layer of the indicating membrane, and chitosan is added with a functional component capable of preventing or absorbing ultraviolet rays as an outer layer of the indicating membrane.

[0006] Sodium alginate is an anionic polysaccharide extracted from brown algae. The film made from it is transparent, non-toxic, biodegradable and has good oxygen barrier properties. It can be used as a food packaging material. The molecular structure of sodium alginate contains a large amount of -COO -, a large number of anions repel each other, making the molecular chain in a stretched state; under acidic conditions, -COO - When converted into -COOH, the molecular chain will shrink; when the pH value continues to increase, -COOH dissociates and the molecular chain will relax; therefore, the molecular chain structure of sodium alginate has a response effect on the pH value. Chitosan is a cationic polysaccharide obtained by deacetylation of chitin, which has good biocompatibility, biodegradability and inherent antibacterial properties, and can be used as a food packaging material. The mechanism of action of the double-layer film provided by the present invention: the present invention utilizes the response of the molecular chain structure of sodium alginate to the pH value, so that anthocyanins are fixed in the sodium alginate matrix in a weakly acidic environment, so that anthocyanins can be stably loaded in the sodium alginate matrix. When the environmental pH value changes (such as when food corruption produces an alkaline microenvironment), the sodium alginate molecular chain relaxes, anthocyanins are released and show different colors with the change of the environmental pH value, thereby realizing the pH value indication of the film. At the same time, a functional component that blocks or absorbs ultraviolet rays is added to the chitosan matrix layer as the outer layer of the indicator film to reduce the influence of ultraviolet rays on anthocyanins and extend the service life of the sodium alginate-chitosan double-layer pH indicator film.

[0007] The invention utilizes the characteristics of sodium alginate anionic polysaccharide and chitosan cationic polysaccharide to form a sodium alginate-chitosan double-layer membrane.

[0008] The present invention provides a method for preparing a chitosan-sodium alginate double-layer membrane with a pH value indicating function, comprising the following steps:

[0009] (1) Preparation of film-forming solution of sodium alginate and anthocyanin:

[0010] Sodium alginate is completely dissolved in deionized water, and then glycerol is added and stirred evenly; the solution is adjusted to a pH value of 4 to 6 using an acidic pH adjusting agent; anthocyanin is further added, and stirred evenly to form a solution to obtain a film-forming solution of sodium alginate and anthocyanin;

[0011] (2) Preparation of chitosan and functional component film-forming solution:

[0012] Dissolve chitosan in an acidic solution, and then evenly disperse the functional components in the chitosan solution; then add a certain amount of glycerol, and use an alkaline pH adjusting agent to adjust the pH value of the solution to 4 to 6, and stir evenly to form a film-forming solution of chitosan and functional components;

[0013] The acidic solution includes one of glacial acetic acid, formic acid, hydrochloric acid, lactic acid, malic acid, ascorbic acid, tartaric acid, and salicylic acid, and the mass concentration of chitosan in the acidic solution is 0.5-5%;

[0014] The order of step (1) and step (2) in the present invention can be reversed;

[0015] (3) Using a film-forming method, the film-forming solutions of step (1) and step (2) are formed into a double-layer composite film.

[0016] The viscosity of the sodium alginate used in the present invention is not particularly required, as long as it can form a film smoothly. A sodium alginate with a viscosity of 100 to 300 mPa·s is preferred. The mechanical properties of sodium alginate with a viscosity less than 100 mPa·s after film formation are poor, and the solubility of sodium alginate with a viscosity greater than 300 mPa·s is poor, and it is not easy to prepare a uniform film-forming solution. The mass concentration of the sodium alginate solution formed by completely dissolving sodium alginate in deionized water is 1 to 3%.

[0017] Glycerol is added to sodium alginate to improve the plasticity of the sodium alginate matrix film and increase the elongation of the film. The amount of glycerol added is 0.02~10% (based on the percentage of sodium alginate). When the amount is large, the performance of the film decreases, and when the amount is small, the effect is not obvious.

[0018] The acidic pH value adjusting agent in the present invention is one or more of organic acids or inorganic acids; wherein the organic acid can be acetic acid, citric acid, lactic acid, malic acid, formic acid, ascorbic acid, etc., and the inorganic acid can be hydrochloric acid, sulfuric acid, phosphoric acid, etc.

[0019] The anthocyanidin in the present invention refers to a glycoside derivative, which can be one or more of blueberry anthocyanidin, purple cabbage anthocyanidin, roselle anthocyanidin, mulberry anthocyanidin, grape skin red pigment, geranium pigment, cornflower pigment, delphinium pigment, peony pigment, morning glory pigment and mallow pigment. The amount of anthocyanidin added is 0.5-10% of the mass of sodium alginate.

[0020] The chitosan used in the present invention has no special requirements, as long as it can form a film smoothly. Chitosan with a viscosity of 100 to 300 mPa·s is preferred. Chitosan with a viscosity of less than 100 mPa·s has poor mechanical properties after film formation, and chitosan with a viscosity of more than 300 mPa·s has poor solubility and is not easy to prepare a uniform film-forming solution. The deacetylation degree of chitosan is preferably above 65%, more preferably above 90%.

[0021] In the present invention, chitosan can be dissolved in other solvents or solvent systems to form a chitosan film-forming solution. From the perspective of cost and application in the food field, acetic acid is preferably used as the solvent.

[0022] The functional component described in the present invention refers to a substance that can block or absorb ultraviolet rays. From the perspective of cost and application in the food field, it is preferably one or more of titanium dioxide, silicon dioxide or zinc oxide particles. The particle size of the particles is ≤300nm, preferably ≤100nm, and more preferably ≤50nm. The mass percentage of the added functional component particles is 0.05~1.5% (based on the mass of chitosan as 100%), preferably 0.1~1%, and more preferably 0.5~0.8%. When the mass fraction of the functional component particles is low (less than 0.05%), the effect of blocking or absorbing ultraviolet rays is weak, and it cannot play a role in shielding ultraviolet rays to protect the stability of anthocyanins; when the mass fraction of the functional component particles is high (greater than 1.5%), it is not easy to disperse, which increases the cost, and also reduces the mechanical properties of the film, affecting the fluidity and film-forming properties of the film-forming liquid.

[0023] Glycerol is added to chitosan to improve the plasticity of the chitosan matrix film and increase the elongation of the film. The amount of glycerol added is 0.05~8% (based on 100% chitosan solution). When the amount is large, the performance of the film decreases, and when the amount is small, the effect is not obvious.

[0024] The alkaline pH value adjusting agent in the present invention is an alkaline substance, and specifically can be one of sodium hydroxide, sodium carbonate, ammonia water, and sodium bicarbonate.

[0025] In the present invention, any method can be used as long as the sodium alginate film-forming liquid and the chitosan film-forming liquid can form a double-layer film. The preferred film-forming method is a layer-by-layer casting method, an extrusion method or a layered film-forming method.

[0026] The layer-by-layer casting film forming method described in the present invention refers to using a casting method to form a sodium alginate film-forming liquid and a chitosan film-forming liquid in sequence to finally form a sodium alginate-chitosan double-layer film; or chitosan film-forming liquid and a sodium alginate film-forming liquid can be formed in sequence to finally form a sodium alginate-chitosan double-layer film. The base film carrier used in the casting method can be any as long as it can form a sodium alginate-chitosan double-layer film, preferably one or more of glass, cloth (non-woven cloth, woven cloth, knitted cloth, etc.), plastic film, release paper, etc.

[0027] The extrusion method described in the present invention refers to extruding the sodium alginate film-forming liquid and the chitosan film-forming liquid through a die simultaneously or successively to form a double-layer film after drying; the sodium alginate film-forming liquid and the chitosan film-forming liquid can also be extruded through a die simultaneously or successively into a coagulation liquid to coagulate the film-forming liquid to form a sodium alginate-chitosan double-layer film.

[0028] The layered film forming method described in the present invention refers to first using sodium alginate film-forming liquid to form a sodium alginate film, and then using chitosan film-forming liquid to form a chitosan film on the sodium alginate film, and finally forming a sodium alginate-chitosan double-layer film; or first using chitosan film-forming liquid to form a chitosan film, and then using alginate film-forming liquid to form a sodium alginate film on the chitosan film, and finally forming a sodium alginate-chitosan double-layer film.

[0029] Beneficial effects of the present invention:

[0030] (1) The chitosan-sodium alginate double-layer film prepared by the present invention utilizes the response characteristics of the sodium alginate molecular chain structure to pH value to load and fix anthocyanins. When the pH value of the environment changes (such as when protein corruption produces a slightly alkaline environment), anthocyanins can be quickly released from the film and display different colors, thereby achieving an indication of the pH value. It can be used to monitor the freshness of meat products in real time.

[0031] (2) The chitosan layer of the chitosan-sodium alginate double-layer membrane of the present invention contains a substance that can block or absorb ultraviolet rays, which effectively improves the utilization rate and stability of anthocyanins in the sodium alginate layer, increases the pH indication time of the chitosan-sodium alginate double-layer membrane, and prolongs the service life of the chitosan-sodium alginate double-layer membrane.

[0032] (3) The sodium alginate and chitosan used in the chitosan-sodium alginate double-layer film of the present invention are both biomass raw materials, and have the advantages of being non-toxic, degradable, low-carbon, and antibacterial, and have better mechanical properties, water vapor barrier properties, antibacterial properties, antioxidant properties, etc. than single-layer sodium alginate and chitosan films. The chitosan-sodium alginate double-layer film of the present invention has potential significant economic and social benefits, and is of great significance for reducing food waste, ensuring food safety, and reducing carbon emissions. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 These are scanning electron microscope images of (a) the surface of the chitosan film layer, (b) the surface of the sodium alginate film layer, and (c) the cross section of the sodium alginate-chitosan double-layer membrane in Example 1 at a magnification of 1000 times.

[0034] Figure 2 The mechanical properties of the sodium alginate-chitosan bilayer films in Examples 1, 2 and 3.

[0035] Figure 3 The color stability of the sodium alginate-chitosan double-layer films in Comparative Examples 1 and 2 and Example 1 at 4°C and 25°C.

[0036] Figure 4 It is the cumulative percentage of anthocyanins released from the sodium alginate-chitosan double-layer film in Example 1 at different pH values.

[0037] Figure 5 This is the color effect of the sodium alginate-chitosan double-layer film in Example 1 under the condition of pH value of 2 to 13. DETAILED DESCRIPTION

[0038] The present invention will be further described in detail below in conjunction with embodiment.It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0039] Example 1

[0040] A chitosan-sodium alginate double-layer membrane with pH value indication function and a preparation method thereof are implemented. The double-layer membrane and the preparation method thereof are:

[0041] Sodium alginate with a viscosity of 200 mPa·s was completely dissolved in deionized water (2.0wt%), and then 5wt% (relative to the mass of sodium alginate) of glycerol was added and stirred evenly. The pH value of the solution was then adjusted to 5 with acetic acid, and 2.5wt% (relative to the mass of sodium alginate) of blueberry anthocyanin was added under stirring at room temperature and dissolved evenly to obtain a sodium alginate film-forming solution. Chitosan with a viscosity of 200 mPa·s (deacetylation degree ≥ 95%) was completely dissolved in 1% (v / v) glacial acetic acid solution (2wt%). 0.8wt% (relative to the mass of chitosan) of titanium dioxide (particle size of about 25 nm) was added to the chitosan solution under stirring conditions, ultrasonically dispersed for 30 min to make the titanium dioxide evenly dispersed, and then 0.8wt% (relative to the mass of chitosan) of glycerol was added. After stirring evenly, the pH value of the chitosan solution was adjusted to 5 with sodium hydroxide to obtain a uniform chitosan film-forming solution. The sodium alginate-chitosan double-layer film was prepared by a layered film-forming method, specifically: the film-scraping thickness was set to 90 μm using an adjustable film-coating machine (accuracy: ±2 μm), the sodium alginate film-forming liquid was coated on a glass plate, and the sodium alginate was allowed to dry naturally at room temperature. Then, the film-scraping thickness of the film-coating machine was set to 85 μm, the chitosan film-forming liquid was coated on the dried sodium alginate film, and the sodium alginate-chitosan double-layer film was allowed to dry naturally at room temperature, and the sodium alginate-chitosan double-layer film was obtained by peeling off the film. Figure 1 The three pictures in the figure correspond to the film images at that location. Since it is a double-layer film, Figure a represents the outer surface morphology of the chitosan layer, Figure b represents the outer surface morphology of the alginate layer, and Figure c is the morphology of the cross-section of the double-layer membrane.

[0042] Example 2

[0043] Sodium alginate with a viscosity of 300 mPa·s was completely dissolved in deionized water (1.0wt%), and then 10wt% (relative to the mass of sodium alginate) of glycerol was added and stirred evenly. The pH value of the solution was then adjusted to 4.0 with citric acid, and 2.0wt% (relative to the mass of sodium alginate) of purple cabbage anthocyanin was added under stirring at room temperature and dissolved evenly to obtain a sodium alginate film-forming solution. Chitosan with a viscosity of 100 mPa·s (deacetylation degree ≥ 65%) was completely dissolved in formic acid solution (2.5wt%). 0.5wt% (relative to the mass of chitosan) of silicon dioxide (particle size of about 300 nm) was added to the chitosan solution under stirring conditions, and the silicon dioxide was evenly dispersed by ultrasonic dispersion for 30 min, and then 0.05wt% (relative to the mass of chitosan) of glycerol was added. After stirring evenly, the pH value of the chitosan solution was adjusted to 4.5 with sodium carbonate to obtain a uniform chitosan film-forming solution. The sodium alginate-chitosan double-layer film was prepared by a layered film-forming method, specifically: the film-scraping thickness was set to 80 μm using an adjustable film-coating machine (accuracy: ±2 μm), the sodium alginate film-forming liquid was coated on the release paper, and the sodium alginate was allowed to dry naturally at room temperature. Then, the film-scraping thickness of the film-coating machine was set to 95 μm, the chitosan film-forming liquid was coated on the dried sodium alginate film, and the sodium alginate-chitosan double-layer film was allowed to dry naturally at room temperature, and the sodium alginate-chitosan double-layer film was obtained by peeling off the film.

[0044] Example 3

[0045] Sodium alginate with a viscosity of 100 mPa·s was completely dissolved in deionized water (3.0wt%), and then 0.02wt% (relative to the mass of sodium alginate) of glycerol was added and stirred evenly. Subsequently, the pH value of the solution was adjusted to 6.0 with lactic acid, and 1.5wt% (relative to the mass of sodium alginate) of roselle anthocyanin was added under stirring at room temperature and dissolved evenly to obtain a sodium alginate film-forming solution. Chitosan with a viscosity of 300 mPa·s (deacetylation degree ≥ 90%) was completely dissolved in a hydrochloric acid solution (1.5wt%). Under stirring conditions, 1wt% (relative to the mass of chitosan) of zinc oxide (particle size of about 80 nm) was added to the chitosan solution, ultrasonically dispersed for 30 min to make the zinc oxide evenly dispersed, and then 8wt% (relative to the mass of chitosan) of glycerol was added. After stirring evenly, the pH value of the chitosan solution was adjusted to 6.0 with ammonia water to obtain a uniform chitosan film-forming solution. The sodium alginate-chitosan double-layer film was prepared by a layered film-forming method, specifically: the film-scraping thickness was set to 70 μm using an adjustable film-coating machine (accuracy: ±2 μm), the sodium alginate film-forming liquid was coated on the non-woven fabric, and the sodium alginate was allowed to dry naturally at room temperature. Then, the film-scraping thickness of the film-coating machine was set to 90 μm, the chitosan film-forming liquid was coated on the dried sodium alginate film, and the sodium alginate-chitosan double-layer film was allowed to dry naturally at room temperature, and the sodium alginate-chitosan double-layer film was obtained by peeling off the film.

[0046] Example 4

[0047] Sodium alginate with a viscosity of 150 mPa·s was completely dissolved in deionized water (2.5wt%), and then 0.08wt% (relative to the mass of sodium alginate) of glycerol was added and stirred evenly. Subsequently, the pH value of the solution was adjusted to 4.5 with hydrochloric acid, and 0.5wt% (relative to the mass of sodium alginate) of mulberry anthocyanin was added under stirring at room temperature and dissolved evenly to obtain a sodium alginate film-forming solution. Chitosan with a viscosity of 250 mPa·s (deacetylation degree ≥ 75%) was completely dissolved in lactic acid solution (1.0wt%). Under stirring conditions, 0.05wt% (relative to the mass of chitosan) of titanium dioxide (particle size of about 30 nm) was added to the chitosan solution, ultrasonically dispersed for 30 min to make the titanium dioxide uniformly dispersed, and then 5wt% (relative to the mass of chitosan) of glycerol was added. After stirring evenly, the pH value of the chitosan solution was adjusted to 4.0 with sodium bicarbonate to obtain a uniform chitosan film-forming solution. The sodium alginate-chitosan double-layer film was prepared by a layered film-forming method, specifically: the film-scraping thickness was set to 65 μm using an adjustable film-coating machine (accuracy: ±2 μm), the sodium alginate film-forming liquid was coated on the woven cloth, and the sodium alginate was allowed to dry naturally at room temperature. Then, the film-scraping thickness of the film-coating machine was set to 75 μm, the chitosan film-forming liquid was coated on the dried sodium alginate film, and the sodium alginate-chitosan double-layer film was allowed to dry naturally at room temperature, and the sodium alginate-chitosan double-layer film was obtained by peeling off the film.

[0048] Example 5

[0049] Sodium alginate with a viscosity of 250 mPa·s was completely dissolved in deionized water (1.5wt%), and then 2wt% (relative to the mass of sodium alginate) of glycerol was added and stirred evenly. Subsequently, the pH value of the solution was adjusted to 4.0 with dilute sulfuric acid, and 1.0wt% (relative to the mass of sodium alginate) of grape skin red pigment was added under stirring at room temperature and dissolved evenly to obtain a sodium alginate film-forming solution. Chitosan with a viscosity of 100 mPa·s (deacetylation degree ≥ 80%) was completely dissolved in malic acid solution (1.8wt%). 1.5wt% (relative to the mass of chitosan) of silicon dioxide (particle size of about 20 nm) was added to the chitosan solution under stirring conditions, and the silicon dioxide was evenly dispersed by ultrasonic dispersion for 30 min, and then 0.1wt% (relative to the mass of chitosan) of glycerol was added. After stirring evenly, the pH value of the chitosan solution was adjusted to 4.5 with sodium hydroxide to obtain a uniform chitosan film-forming solution. The sodium alginate-chitosan double-layer film was prepared by a layered film-forming method, specifically: the film-scraping thickness was set to 65 μm using an adjustable film-coating machine (accuracy: ±2 μm), the sodium alginate film-forming liquid was coated on the plastic film, and the sodium alginate was allowed to dry naturally at room temperature. Then, the film-scraping thickness of the film-coating machine was set to 75 μm, the chitosan film-forming liquid was coated on the dried sodium alginate film, and the sodium alginate-chitosan double-layer film was allowed to dry naturally at room temperature, and the sodium alginate-chitosan double-layer film was obtained by peeling off the film.

[0050] Example 6

[0051] Sodium alginate with a viscosity of 280 mPa·s was completely dissolved in deionized water (1.2wt%), and then 1wt% (relative to the mass of sodium alginate) of glycerol was added and stirred evenly. Subsequently, the pH value of the solution was adjusted to 4.0 with phosphoric acid, and 6.0wt% (relative to the mass of sodium alginate) of geranium pigment was added under stirring at room temperature and dissolved evenly to obtain a sodium alginate film-forming solution. Chitosan with a viscosity of 280 mPa·s (deacetylation degree ≥ 95%) was completely dissolved in ascorbic acid solution (3.5wt%). Under stirring conditions, 0.8wt% (relative to the mass of chitosan) of zinc oxide (particle size of about 100 nm) was added to the chitosan solution, ultrasonically dispersed for 30 min to make the zinc oxide evenly dispersed, and then 6wt% (relative to the mass of chitosan) of glycerol was added. After stirring evenly, the pH value of the chitosan solution was adjusted to 4.0 with sodium carbonate to obtain a uniform chitosan film-forming solution. The sodium alginate-chitosan double-layer film is prepared by a layer-by-layer casting method, specifically: a knitted fabric is laid on a glass or steel plate, the plate is tilted at a certain angle, a sodium alginate film-forming liquid is poured on the plate, the film-forming liquid is naturally cast into a film, and then dried to obtain a sodium alginate film. Then, the chitosan film is obtained by a scraping film method or a similar casting method using the chitosan film-forming liquid, and the sodium alginate-chitosan double-layer film is obtained by peeling off the film after drying.

[0052] Example 7

[0053] Chitosan with a viscosity of 220 mPa·s (degree of deacetylation ≥ 65%) was completely dissolved in a tartaric acid solution (2.8wt%). 1.2wt% (relative to the mass of chitosan) titanium dioxide (particle size of about 50 nm) was added to the chitosan solution under stirring conditions, and the titanium dioxide was evenly dispersed by high-speed stirring. Then 4wt% (relative to the mass of chitosan) glycerol was added, and after stirring evenly, the pH value of the chitosan solution was adjusted to 4.0 with ammonia water to obtain a uniform chitosan film-forming liquid. Sodium alginate with a viscosity of 220 mPa·s was completely dissolved in deionized water (1.4wt%), and then 2.5wt% (relative to the mass of sodium alginate) glycerol was added and stirred evenly. Subsequently, the pH value of the solution was adjusted to 6.0 with malic acid, and 2.5wt% (relative to the mass of sodium alginate) cyanidin was added under stirring at room temperature, and dissolved evenly to obtain a sodium alginate film-forming liquid. The sodium alginate-chitosan double-layer film is prepared by the layered film-forming method, specifically: the film thickness is set to 90 μm with an adjustable film coating machine (accuracy: ±2 μm), the sodium alginate film-forming liquid is coated on the release paper, and the sodium alginate film is obtained by drying the film. Then, the film thickness of the film coating machine is set to 120 μm, the chitosan film-forming liquid is coated on the dried sodium alginate film, and the sodium alginate-chitosan double-layer film is naturally dried at room temperature, and the sodium alginate-chitosan double-layer film is obtained by peeling off the film. The double-layer film can be prepared by the film scraping method using two film scraping machines to perform film scraping operations continuously, that is, one film scraping machine scrapes the film to form a sodium alginate film, and then the formed sodium alginate film is dried by a dryer, and the other film scraping machine continues to scrape the film on the sodium alginate film to form a chitosan film, and the sodium alginate-chitosan double-layer film is obtained after drying. The film-forming order of sodium alginate film and chitosan film can be reversed.

[0054] Example 8

[0055] Chitosan with a viscosity of 150 mPa·s (degree of deacetylation ≥ 85%) was completely dissolved in salicylic acid solution (1.6wt%). 1wt% (relative to the mass of chitosan) zinc oxide (particle size of about 10 nm) was added to the chitosan solution under stirring conditions, and the zinc oxide was evenly dispersed by ultrasound, and then 1wt% (relative to the mass of chitosan) glycerol was added. After stirring, the pH value of the chitosan solution was adjusted to 6.0 with sodium bicarbonate to obtain a uniform chitosan film-forming solution. Sodium alginate with a viscosity of 150 mPa·s was completely dissolved in deionized water (2.5wt%), and then 4wt% (relative to the mass of sodium alginate) glycerol was added and stirred evenly. Subsequently, the pH value of the solution was adjusted to 5.5 with malic acid and acetic acid, and 8.0wt% (relative to the mass of sodium alginate) delphinium pigment was added under stirring at room temperature and dissolved evenly to obtain a sodium alginate film-forming solution. The double-layer film is prepared by a co-extrusion method, specifically, a sodium alginate film-forming liquid and a chitosan film-forming liquid are extruded through a two-component die simultaneously, and a sodium alginate-chitosan double-layer film is formed after drying.

[0056] Example 9

[0057] Sodium alginate with a viscosity of 160 mPa·s was completely dissolved in deionized water (2.2wt%), and then 1.5wt% (relative to the mass of sodium alginate) of glycerol was added and stirred evenly. Subsequently, the pH value of the solution was adjusted to 6.0 with lactic acid and citric acid, and 1.2wt% (relative to the mass of sodium alginate) of peony pigment was added under stirring at room temperature and dissolved evenly to obtain a sodium alginate film-forming solution. Chitosan with a viscosity of 240 mPa·s (deacetylation degree ≥ 90%) was completely dissolved in acetic acid solution (2.4wt%). Under stirring conditions, 1wt% (relative to the mass of chitosan) of zinc oxide and titanium dioxide (1:1) (particle size of about 150 nm) were added to the chitosan solution, and ultrasound was used to disperse the functional components evenly, and then 3wt% (relative to the mass of chitosan) of glycerol was added. After stirring evenly, the pH value of the chitosan solution was adjusted to 5.5 with sodium hydroxide and sodium carbonate to obtain a uniform chitosan film-forming solution. The preparation process of sodium alginate-chitosan double-layer film is as follows: firstly, the sodium alginate film-forming liquid is extruded through a die, and a sodium alginate film is formed after drying; then, a chitosan film layer is formed on the sodium alginate film by a scraping film method, and finally a sodium alginate-chitosan double-layer film is obtained.

[0058] Example 10

[0059] Sodium alginate with a viscosity of 240 mPa·s was completely dissolved in deionized water (1.5wt%), and then 6wt% (relative to the mass of sodium alginate) of glycerol was added and stirred evenly. The pH value of the solution was then adjusted to 4.0 with formic acid, and 1.8wt% (relative to the mass of sodium alginate) of morning glory pigment was added under stirring at room temperature and dissolved evenly to obtain a sodium alginate film-forming solution. Chitosan with a viscosity of 180 mPa·s (deacetylation degree ≥ 65%) was completely dissolved in a formic acid solution (2.0wt%). 1wt% (relative to the mass of chitosan) of titanium dioxide and silicon dioxide (1:2) (particle size of about 50 nm) was added to the chitosan solution under stirring conditions, and the functional components were evenly dispersed by ultrasound, and then 2wt% (relative to the mass of chitosan) of glycerol was added. After stirring evenly, the pH value of the chitosan solution was adjusted to 6.0 with sodium bicarbonate and ammonia water to obtain a uniform chitosan film-forming solution. The preparation process of sodium alginate-chitosan double-layer film is: first, the chitosan film-forming liquid is extruded through a die, and a chitosan film is formed after drying; then, a sodium alginate film layer is formed on the chitosan film by a scraping method, and finally a sodium alginate-chitosan double-layer film is obtained.

[0060] Embodiment 11

[0061] Sodium alginate with a viscosity of 180 mPa·s was completely dissolved in deionized water (1.0wt%), and then 3wt% (relative to the mass of sodium alginate) of glycerol was added and stirred evenly. Subsequently, the pH value of the solution was adjusted to 4.0 with ascorbic acid, and 10wt% (relative to the mass of sodium alginate) of malva pigment was added under stirring at room temperature and dissolved evenly to obtain a sodium alginate film-forming solution. Chitosan with a viscosity of 160 mPa·s (deacetylation degree ≥ 70%) was completely dissolved in a hydrochloric acid solution (1.0wt%). Under stirring conditions, 0.5wt% (relative to the mass of chitosan) of zinc oxide and silicon dioxide (3:1) (particle size of about 30 nm) were added to the chitosan solution, and high-speed stirring was performed to evenly disperse the functional components, and then 1.5wt% (relative to the mass of chitosan) of glycerol was added. After stirring evenly, the pH value of the chitosan solution was adjusted to 4.0 with ammonia water and sodium hydroxide to obtain a uniform chitosan film-forming solution. The sodium alginate-chitosan double-layer film was prepared by a layered film-forming method, specifically: the film-scraping thickness was set to 50 μm using an adjustable film-coating machine (accuracy: ±2 μm), the sodium alginate film-forming liquid was coated on the non-woven fabric, and the sodium alginate was allowed to dry naturally at room temperature. Then, the film-scraping thickness of the film-coating machine was set to 85 μm, the chitosan film-forming liquid was coated on the dried sodium alginate film, and the sodium alginate-chitosan double-layer film was allowed to dry naturally at room temperature, and the sodium alginate-chitosan double-layer film was obtained by peeling off the film.

[0062] Comparative Example 1

[0063] Compared with Example 1, Comparative Example 1 has no chitosan film layer to protect the sodium alginate film layer, and is a sodium alginate single-layer film. The specific steps are as follows:

[0064] Sodium alginate with a viscosity of 200 mPa·s was completely dissolved in deionized water (2wt%), and then 5wt% (relative to the mass of sodium alginate) of glycerol was added and stirred evenly. The pH value of the solution was then adjusted to 5 with acetic acid, and 2.5wt% (relative to the mass of sodium alginate) of blueberry anthocyanin was added under stirring at room temperature and dissolved evenly to obtain a sodium alginate film-forming liquid. The adjustable film coating machine (accuracy: ±2 μm) was set to a film thickness of 90 μm, and the above sodium alginate film-forming liquid was coated on a glass plate, and the sodium alginate was allowed to dry naturally at room temperature, and the sodium alginate film was obtained by peeling off the film.

[0065] Comparative Example 2

[0066] Compared with Example 1, in Comparative Example 2, no titanium dioxide functional component is added to the chitosan film-forming liquid, and the specific steps are the same as those in Example 1.

[0067] The performance test data are as follows:

[0068] (1) Surface and cross-sectional micromorphology of the sodium alginate-chitosan bilayer membrane in Example 1

[0069] Scanning electron microscope photos of the inner and outer surfaces and cross-section of the double-layer membrane (see Appendix Figure 1 ), it can be seen that the film surface is flat, titanium dioxide is evenly distributed, the double-layer film structure has a clear interface on the cross section, but the double layers are tightly connected, and the thickness of the double-layer film is 24 μm.

[0070] (2) Mechanical properties of the double-layer film in Example 1

[0071] The double-layer film was cut into rectangular specimens of 2 cm × 5 cm to ensure that the cut was flat and defect-free. The thickness was measured at three random points of the film test gauge using a thickness gauge (Shanghai Bonte Testing Equipment Manufacturing Co., Ltd.). The upper and lower clamping lengths of the film were both 1 cm, and the middle 3 cm was the test gauge. The tensile strength and elongation at break of the film were measured by a universal texture analyzer (EZ-LX, Shimadzu, Japan) at 5 mm·min -1 During the experiment, the maximum load and the corresponding fracture gauge length when the film broke were recorded. The following formula was used to calculate the film's tensile strength to be 24.40 MPa and its elongation at break to be 39.68% (see Appendix Figure 2 ).

[0072] Tensile strength = maximum load at break / (sample width × sample thickness)

[0073] Elongation at break = (gauge length after specimen fracture - gauge length measured before specimen test) / gauge length measured before specimen test × 100%

[0074] (3) Comparative Study on Film Color Stability in Examples 1 and 2 and Example 1

[0075] The films in Comparative Examples 1 and 2 and Example 1 were stored under normal light at 4°C (a) and 25°C (b), respectively. The color parameters of the films were collected daily using a colorimeter (SR-62, 3nh, China). The color stability of the films was expressed by the larger the change in ΔE, the worse the stability of the films (see Appendix). Figure 3 ), it can be seen that compared with Comparative Examples 1 and 2, Example 1 has the best color stability.

[0076] (4) Anthocyanin release experiment in the film at different pH values ​​in Example 1

[0077] The release behavior of the film at different pH values ​​was studied by release test. Five 2 cm × 2 cm films (blueberry anthocyanin content 0.09 mg) were immersed in a conical flask containing 10 ml of pH 4 to 9 citric acid / sodium hydrogen phosphate buffer and shaken at 150 rpm in a 25°C water bath oscillator for 5 h. Using the pH differential technique, the cyanidin-3-O-glucoside content in the extract was measured every 5 min to calculate the release amount of blueberry anthocyanin in the film. The anthocyanin release amounts were 34.19% at pH 4, 44.59% at pH 5, 49.89% at pH 6, 50.98% at pH 7, 60.94% at pH 8, and 63.62% at pH 9 (see Appendix). Figure 4 ), the results showed that in weakly acidic conditions, anthocyanins were anchored in the inner layer and could be released in alkaline environments, achieving the film's antibacterial and antioxidant properties as well as real-time freshness monitoring properties.

[0078] (5) pH value indication function of the double-layer membrane in Example 1

[0079] The film was cut into 2 cm × 2 cm pieces and immersed in a citric acid / sodium hydrogen phosphate buffer solution with a pH value of 2 to 13 for 5 min, then the film was collected and dried. A colorimeter (SR-62, 3nh, China) was used to read the L, a, b, and ΔE of the film. The color parameters of the double-layer film are shown in Figure 5 As shown, it can be seen that the film changes from red to purple, then to blue, and finally to brown.

Claims

1. A chitosan-sodium alginate double-layer membrane with pH value indication, characterized in that: The sodium alginate matrix is ​​loaded with anthocyanin as the inner layer of the indicator membrane, and chitosan is added with a functional component capable of blocking or absorbing ultraviolet rays as the outer layer of the indicator membrane; the functional component is one or more of titanium dioxide, silicon dioxide or zinc oxide; The method for preparing the chitosan-sodium alginate double-layer membrane with pH value indication function comprises the following steps: (1) Preparation of film-forming solution of sodium alginate and anthocyanin: Completely dissolve sodium alginate in deionized water, then add glycerol and stir evenly; then adjust the pH value of the solution to 4-6 with an acidic pH adjusting agent; further add anthocyanin, stir evenly to form a solution, and obtain a film-forming solution of sodium alginate and anthocyanin; (2) Preparation of chitosan and functional component film-forming solution: Dissolve chitosan in an acidic solution, and then evenly disperse the functional components in the chitosan solution; then add glycerol, and adjust the pH value of the solution to 4-6 with an alkaline pH adjusting agent, and stir evenly to form a film-forming solution of chitosan and functional components; (3) using a film-forming method to form a double-layer composite film from the film-forming solutions of step (1) and step (2); The characteristics of sodium alginate anionic polysaccharide and chitosan cationic polysaccharide are utilized to form a sodium alginate-chitosan double-layer membrane; anthocyanins are fixed in the sodium alginate matrix in a weakly acidic environment, so that anthocyanins can be stably loaded in the sodium alginate matrix; when the environmental pH value changes, the sodium alginate molecular chain relaxes, anthocyanins are released and show different colors as the environmental pH value changes, thereby realizing the pH value indication function of the double-layer membrane.

2. The chitosan-sodium alginate double-layer membrane with pH value indication according to claim 1, characterized in that: The viscosity of the sodium alginate is 100-300 mPa·s; the viscosity of the chitosan is 100-300 mPa·s; and the deacetylation degree of the chitosan is above 65%.

3. The chitosan-sodium alginate double-layer membrane with pH value indication according to claim 1, characterized in that: Anthocyanin refers to a glycoside derivative, and one or more of blueberry anthocyanin, purple cabbage anthocyanin, roselle anthocyanin, mulberry anthocyanin, grape skin red pigment, geranium pigment, cornflower pigment, delphinium pigment, peony pigment, morning glory pigment or mallow pigment is selected; the added amount of anthocyanin is 0.5-10% of the mass of sodium alginate.

4. The chitosan-sodium alginate double-layer membrane with pH value indication according to claim 1, characterized in that: The particle size of the functional component particles is ≤300nm; based on chitosan, the mass percentage of the added functional component particles is 0.05-1.5%.

5. The chitosan-sodium alginate double-layer membrane with pH value indication according to claim 1, characterized in that: In step (1), the mass concentration of the sodium alginate solution formed by completely dissolving sodium alginate in deionized water is 1-3%; the amount of glycerol added is 0.02-10% based on sodium alginate; the acidic pH value adjusting agent is one or more of organic acids or inorganic acids; wherein the organic acid is one of acetic acid, citric acid, lactic acid, malic acid, formic acid, and ascorbic acid, and the inorganic acid is one of hydrochloric acid, sulfuric acid, and phosphoric acid.

6. The chitosan-sodium alginate double-layer membrane with pH value indication according to claim 1, characterized in that: In step (2), the acidic solution includes one of glacial acetic acid, formic acid, hydrochloric acid, lactic acid, malic acid, ascorbic acid, tartaric acid, and salicylic acid; the mass concentration of chitosan in the acidic solution is 0.5-5%; Based on chitosan, the amount of glycerol added is 0.05~8%; The alkaline pH adjusting agent is an alkaline substance, including one of sodium hydroxide, sodium carbonate, ammonia water, and sodium bicarbonate.

7. The chitosan-sodium alginate double-layer membrane with pH value indication according to claim 1, characterized in that: In step (3), the film forming method is a layer-by-layer casting film forming method, an extrusion method or a layered film forming method.

8. The chitosan-sodium alginate double-layer membrane with pH value indication according to claim 7, characterized in that: The layer-by-layer tape casting method refers to using a tape casting method to form a sodium alginate film-forming liquid and a chitosan film-forming liquid in sequence to finally form a sodium alginate-chitosan double-layer film; or to use a chitosan film-forming liquid and a sodium alginate film-forming liquid in sequence to finally form a chitosan-sodium alginate double-layer film; the bottom film carrier used in the tape casting method is selected from one or more of glass, cloth, plastic film, and release paper; The extrusion method refers to extruding the sodium alginate film-forming liquid and the chitosan film-forming liquid through a die simultaneously or successively to form a double-layer film after drying; or extruding the sodium alginate film-forming liquid and the chitosan film-forming liquid through a die simultaneously or successively into a coagulation liquid, so that the film-forming liquid is coagulated to form a sodium alginate-chitosan double-layer film; The layered film forming method refers to first using sodium alginate film-forming liquid to form a sodium alginate film, then using chitosan film-forming liquid to form a chitosan film on the sodium alginate film, and finally forming a sodium alginate-chitosan double-layer film; or first using chitosan film-forming liquid to form a chitosan film, then using alginate film-forming liquid to form a sodium alginate film on the chitosan film, and finally forming a sodium alginate-chitosan double-layer film.

Citation Information

Patent Citations

  • Blueberry anthocyanin edible composite film and preparation method thereof

    CN113045802A

  • Preparation method of chitosan-blueberry anthocyanin edible film

    CN114409975A

  • Preparation method of nano-sized double-layer degradable packaging film with antibacterial function

    CN106317723A

  • Bio-based food freshness indicating film and preparation method thereof

    CN114381042A

Cited By

  • A temperature and humidity responsive controlled release material with polymer-coated γ-CD-MOF antibacterial particles, and a preparation method and application thereof

    CN122750003A